Variation with graphene oxide doping of structural, optical, dielectric and thermal properties of BaCO3:ZnO nanocrystals synthesized by solgel combustion method - Aydin, H.; Taskin, M.; Aydin, C.; Dagdelen, F.; Kaygili, O.; Bulut, N.; Orhan, A. (Springer, 2020)
The results obtained from thermogravimetric (TG) analysis, X-ray diffraction analysis, optical characterization and dielectric measurements of the samples were investigated. In X-ray diffraction patterns, the presence of both BaCO3 and ZnO peaks showed that ZnO and BaCO3 nanocrystals were independently grown. Changes in the band peak position in the FTIR spectra showed that the chemical structure of Ba:Zn nanocomposites changed with the doping of graphene oxide. The optical band gap (E-g) of the samples was calculated as 3.18, 3.19, 3.2, 3.21 and 3.23 eV for BaZn, BaZn25, BaZn50, BaZn75 and BaZn100, respectively. It was determined that the dielectric constants and dielectric losses of the nanocomposites exhibited normal dielectric behavior, decreased with the frequency described in light of Maxwell-Wagner model and increased with increasing graphene oxide concentration. TG measurement showed that the mass loss in the sample decreased with increasing graphene oxide.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: Thermal properties; Ba; Zn nanocomposites; Dielectric measurements; Graphene oxide